Нгоньяма Желтогривый: [повести : перевод с английского] - Гленвилл Эрнест (Сантакс-пресс, 1996)
Экземпляры: аб. (1997) / Инвентарный номер: 39507 / Цена: / Сис.шифр: 84(3) / Авт.знак: Г 53 / ГРНТИ: 17.82.93 / ББК: 84(3)